Three-dimensional carbon polyurethane foam@ hydroxy soddy materials and preparation and aldehyde removal applications thereof

CN117839683BActive Publication Date: 2026-10-09CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311643280.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-04
Publication Date
2026-10-09
Estimated Expiration
2043-12-04

AI Technical Summary

Technical Problem

[0004]虽然,现有的二氧化锰基催化活性材料可以表现出优异的甲醛催化效果,但对低浓度的甲醛的深度脱除效果仍有待提高,不仅如此,现有的催化活性材料主要为粉末或者颗粒,其在实验室阶段可以获得良好的效果,但在实际应用过程中,分散性较差,还容易导致粉尘二次污染

Benefits of technology

[0030] This invention innovatively pre-oxidizes CPF on its surface, then reacts it with potassium permanganate and sugar compounds under ultrasonic and microwave assistance. Furthermore, by precisely controlling the proportions, microwave power, ultrasonic power, temperature, and time during the reaction process, it unexpectedly solves the problem of manganese dioxide being difficult to deposit uniformly on the surface of the framework due to the physicochemical structure of CPF, avoids the aggregation of manganese dioxide, and helps to improve the catalytic active sites, thereby synergistically improving the deep formaldehyde removal capability under low formaldehyde content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117839683B_ABST
    Figure CN117839683B_ABST
Patent Text Reader

Abstract

The application belongs to the field of air pollution treatment, and specifically discloses a preparation method of three-dimensional carbon polyurethane foam@hydroxyl sodamanganite material, which comprises the following steps: performing surface oxidation treatment on three-dimensional carbon polyurethane foam, mixing the three-dimensional carbon polyurethane foam with a potassium permanganate and a saccharide compound in liquid phase, and then performing reaction under the assistance of ultrasonic and microwave to obtain the three-dimensional carbon polyurethane foam@hydroxyl sodamanganite material; during the reaction, the ultrasonic power is 980-1020 W, the microwave power is 500-700 W, the temperature is 55-65 DEG C, the time is 25-35 min, and the weight ratio of the three-dimensional carbon polyurethane foam to the potassium permanganate is 1:1.5-2.5. The application also includes the material prepared by the preparation method and the application of the material in defoaming. The material prepared by the application has excellent formaldehyde removal capacity and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of air pollution treatment, specifically to a formaldehyde treatment method. Background Technology

[0002] Formaldehyde (HCHO) is a major indoor air pollutant that poses a significant threat to human health. Currently, catalytic oxidation, a method for the direct degradation of formaldehyde at room temperature, has attracted widespread attention.

[0003] MnO x With its variable valence state and abundant structural defects, manganese dioxide (MnO2) exhibits promising application prospects for efficient formaldehyde removal. Existing technologies have reported some methods for preparing and improving manganese dioxide formaldehyde removal materials. For example, Chinese patent document CN115845876A discloses a method for the deactivation and regeneration of layered manganese dioxide catalysts for room-temperature formaldehyde degradation. Specifically, the deactivated catalyst is first heated at no more than 250°C, then the active components on the catalyst surface are replenished by ultrasonic impregnation with an alkaline solution. Finally, the catalyst is ultrasonically soaked in a pore-forming agent solution under vacuum, dried, and calcined to obtain a layered manganese dioxide catalyst with restored activity. Another example is Chinese patent document CN114452974A, which discloses a microwave-ultrasound-assisted preparation method for MnO2-based formaldehyde removal materials. A mixed solution containing permanganate and a reducing organic carbon source is reacted under the combined assistance of ultrasound and microwave to obtain the MnO2-based formaldehyde removal material.

[0004] While existing manganese dioxide-based catalytic materials exhibit excellent formaldehyde catalytic effects, their effectiveness in removing low concentrations of formaldehyde still needs improvement. Furthermore, these materials are primarily in powder or granular form, which, while achieving good results in laboratory settings, suffer from poor dispersibility and are prone to secondary dust pollution in practical applications. Theoretically, loading manganese dioxide-based active materials onto a carrier could solve the problem of secondary powder pollution; however, inappropriate loading processes can easily block and restrict active sites, further limiting the effectiveness of deep formaldehyde removal in low-formaldehyde concentration environments. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the primary objective of this invention is to provide a three-dimensional carbon polyurethane foam@water sodium manganese ore material (CPF@MnO) x The preparation method aims to obtain a new material that still has the ability to deeply remove low formaldehyde content.

[0006] The second objective of this invention is to provide a three-dimensional carbon polyurethane foam@sodium manganese ore material prepared by the aforementioned method and its application in formaldehyde removal.

[0007] In laboratory testing, most studies use simulated systems with high formaldehyde concentrations to test the performance of formaldehyde removal materials. While these materials generally exhibit good formaldehyde removal effects in high-concentration systems, in real-world applications, environmental formaldehyde levels are typically low. In such systems, these materials often struggle to maintain their superior deep formaldehyde removal performance. To address this issue, this invention is the first in the industry to propose loading manganese dioxide (especially hydrated manganese dioxide) onto three-dimensional carbon polyurethane foam (CPF). However, earlier research has shown that CPF has characteristics such as low specific gravity, hydrophobic surface, and abundant three-dimensional nanopores. This increases the difficulty of uniformly depositing manganese dioxide onto the framework and nano-three-dimensional pore structure, failing to effectively solve the problems of manganese dioxide grain agglomeration and active site shielding, thus affecting the formaldehyde treatment performance of the composite material, particularly its deep formaldehyde removal capability in low-formaldehyde systems. To address this problem, this invention, after in-depth research, provides the following improvement:

[0008] A method for preparing three-dimensional carbon polyurethane foam@sodium manganese ore material involves surface oxidation treatment of three-dimensional carbon polyurethane foam, followed by liquid-phase mixing with potassium permanganate and sugar compounds, and then reacting under ultrasonic and microwave assistance to obtain the three-dimensional carbon polyurethane foam@sodium manganese ore material.

[0009] During the reaction, the ultrasonic power was 980–1020 W, the microwave power was 500–700 W, the temperature was 55–65 °C, the time was 25–35 min, and the weight ratio of three-dimensional carbon polyurethane foam to potassium permanganate was 1:1.5–2.5.

[0010] To address the problem that the low specific gravity, high hydrophobicity, and abundant nanopores of CPF make it difficult for manganese dioxide to be uniformly deposited on the framework, resulting in unsatisfactory deep formaldehyde removal performance of the composite material in low formaldehyde systems, this invention innovatively pre-oxidizes the surface of CPF and then reacts it with potassium permanganate and sugar compounds under ultrasonic and microwave assistance. Furthermore, by precisely controlling the CPF / potassium permanganate ratio, microwave power, ultrasonic power, temperature, and time during the reaction process, this unexpectedly solves the problem of the difficulty in uniformly depositing manganese dioxide on the framework surface caused by the physicochemical characteristics of CPF, avoids manganese dioxide agglomeration, and helps improve catalytic active sites, thereby synergistically improving the deep formaldehyde removal capability under low formaldehyde content.

[0011] In this invention, the combined control of CPF pretreatment, CPF / potassium permanganate ratio, ultrasonic and microwave assisted reaction power, microwave power, reaction temperature and time is the key to synergistically solving the problems caused by the physicochemical structural characteristics of CPF and improving the deep removal effect of low-concentration formaldehyde.

[0012] In this invention, the carbon polyurethane foam can be a conventional commercially available product. For example, the carbon polyurethane foam has a mesh size of 10-30 PPI and a tensile strength of 0.1-0.2 MPa.

[0013] In this invention, the surface oxidation treatment includes immersing the three-dimensional carbon polyurethane foam in a dilute nitric acid solution, followed by washing with water until neutral and drying.

[0014] In this invention, the concentration of the dilute nitric acid is 0.5–3 M;

[0015] In this invention, the soaking time is more than 1 hour, preferably 2 to 10 hours.

[0016] In this invention, the weight ratio of three-dimensional carbon polyurethane foam to potassium permanganate is 1:1.8 to 2.2.

[0017] In this invention, the carbohydrate compound is at least one of glucose, sucrose, and chitosan.

[0018] In this invention, the three-dimensional carbon polyurethane foam with surface oxidation treatment is placed in a reaction vessel beforehand, and then a mixed solution containing potassium permanganate and water-soluble sugar compounds is added dropwise to carry out liquid phase mixing;

[0019] Alternatively, water-soluble sugars can be pre-adsorbed onto the three-dimensional carbon polyurethane foam after surface oxidation treatment, and then mixed with a potassium permanganate solution in the liquid phase. This invention demonstrates that the preferred processing method can further address the problem of uneven manganese dioxide deposition on the framework caused by the high hydrophobicity and high nanopore content of CPF itself.

[0020] In this invention, the weight ratio of potassium permanganate to carbohydrate compound is 1:0.1 to 0.2, preferably 1:0.13 to 0.18, and more preferably 1:0.14 to 0.16.

[0021] In this invention, the liquid-phase mixture system containing CPF, potassium permanganate, and carbohydrate compounds is subjected to the reaction under the dual assistance of ultrasound and microwave. The precise control of the ultrasound and microwave power, temperature, and time during the reaction process unexpectedly achieves synergy, which can solve the problem of the difficulty in uniformly depositing manganese dioxide due to the hydrophobic nature and high nanopores of CPF itself.

[0022] In this invention, after the reaction is completed, solid-liquid separation is performed, followed by water washing, alcohol washing, and drying to obtain the three-dimensional carbon polyurethane foam@sodium manganese ore material.

[0023] The present invention also provides a three-dimensional carbon polyurethane foam@sodium manganese ore material prepared by the preparation method described above.

[0024] The preparation method described in this invention can endow the prepared material with physicochemical characteristics, and the material prepared by the method has better performance. For example, it can still show excellent deep formaldehyde removal effect in systems with low formaldehyde concentration.

[0025] This invention also provides an application of the three-dimensional carbon polyurethane foam@sodium manganese ore material prepared by the above preparation method, which is used as a formaldehyde removal material to remove formaldehyde content from the gas to be treated.

[0026] In this invention, the material, thanks to its excellent formaldehyde removal ability, can be applied to any formaldehyde system. However, for application scenarios with low formaldehyde content, it can obtain better application value compared with the existing technology. Thus, in the method of this invention, the initial formaldehyde content in the gas to be treated can be controlled below 20 ppm, preferably 10 to 15 ppm.

[0027] Preferably, the initial humidity of the gas to be treated during the removal process is 55-65%;

[0028] Preferably, the temperature during the removal process is room temperature.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] This invention innovatively pre-oxidizes CPF on its surface, then reacts it with potassium permanganate and sugar compounds under ultrasonic and microwave assistance. Furthermore, by precisely controlling the proportions, microwave power, ultrasonic power, temperature, and time during the reaction process, it unexpectedly solves the problem of manganese dioxide being difficult to deposit uniformly on the surface of the framework due to the physicochemical structure of CPF, avoids the aggregation of manganese dioxide, and helps to improve the catalytic active sites, thereby synergistically improving the deep formaldehyde removal capability under low formaldehyde content.

[0031] The synthesis process of this invention is simple, the raw materials are inexpensive, the preparation conditions are mild, it does not involve any high temperature or high pressure operations, and the reaction time is short, so it is easy to promote industrial production and marketization.

[0032] This invention establishes a molded body @MnO x Composite material synthesis methods utilize the physical spatial expansion effect of the shaped material structure to increase MnO x This increases the degree of dispersion and improves its contact with formaldehyde molecules. Attached Figure Description

[0033] Figure 1 MnO in Examples 1 and 2 x The curve showing the change in loading on the CPF over deposition time.

[0034] Figure 2XRD patterns of the room-temperature aldehyde removal composite catalysts prepared for different treatment groups in Examples 1 and 2.

[0035] Figure 3 SEM images of the room-temperature aldehyde removal composite catalysts prepared in different treatment groups of Examples 1 and 2.

[0036] Figure 4 The data represent the formaldehyde removal results of Example 1 and Comparative Example 4. Detailed Implementation

[0037] The present invention will be further described in detail below through embodiments and in conjunction with the accompanying drawings.

[0038] In this invention, the carbon polyurethane foam can be a commercially available product. For example, as a typical example, the carbon polyurethane foam in this invention is from Nantong Senyou Carbon Fiber Co., Ltd.; the product name is activated carbon sponge; the model number is SY-GAC-2001; and the item number is 45142.

[0039] Example 1

[0040] (1) Cut the prepared 3mm thick carbon polyurethane foam into a 10*10mm square, then immerse it in 1M dilute nitric acid for 6 hours, then ultrasonically clean it with deionized water until the water is neutral, and dry it to obtain modified CPF.

[0041] (2) Weigh a certain mass of potassium permanganate into a 250 mL beaker, add 100 mL of deionized water, and dissolve it evenly by sonication and stirring to obtain a purple solution A; then weigh a certain mass of glucose and dissolve it completely in 5 mL of deionized water to obtain a transparent solution B. Quickly mix solution A and solution B and stir evenly to obtain solution C, wherein the mass ratio of glucose to potassium permanganate is 0.15:1;

[0042] (3) Place the carbon polyurethane foam prepared in step (1) into the reaction chamber and add it into solution C, ensuring that it is immersed in the solution. The weight ratio of the three-dimensional carbon polyurethane foam to potassium permanganate is 1:2.

[0043] (4) Transfer the solution C containing carbon polyurethane foam to a microwave-ultrasonic reactor, set the target temperature to 60℃ (reaction temperature), ultrasonic power to 1000W, microwave power to 600W, and reaction time to 30min.

[0044] (5) Three-dimensional CPF@MnO can be obtained by washing with deionized water and anhydrous ethanol and then drying. x .

[0045] Example 2: Study on Synthesis Time

[0046] Compared to Example 1, the only difference is that the reaction time in step 4 is changed, and the experimental groups are as follows:

[0047] Group A: 15 min, denoted as CPF@MnO x Group A: 15 min; Group B: 30 min (i.e., Example 1), denoted as CPF@MnO x -30min; Group C: 60min, denoted as CPF@MnO x -60min; Group d: 120min, denoted as CPF@MnO x -120min.

[0048] Load variation over time:

[0049] Figure 1 MnO x The loading on CPF changed over time, and it was found that in the first 30 minutes of the reaction, the MnO content in the synthesized product was highest. x The loading increased almost linearly with reaction time, reaching 5.163 mg·cm³ after 30 min. -1 However, when the deposition time was further increased to 60 min and 120 min, the loading increased from 6.708 mg·cm³. -1 Slowly increased to 7.040 mg·cm³ -1 The growth rate is slow. Therefore, MnO x Effective deposition occurred within the first 30 minutes on the CPF, while the deposition rate slowed down after 30 minutes, possibly due to the gradual occupancy of macroscopic channels, consistent with the SEM analysis results below.

[0050] XRD analysis:

[0051] Figure 2 This demonstrates the effects of CPF without any loading and CPF@MnO prepared at different deposition times. x XRD pattern of the composite. Related studies have shown that the broad diffraction peak at 23.3° can be attributed to the poorly graphitized carbon (002) crystal plane. Meanwhile, the diffraction peak at 36.5°, after comparison with the PDF standard card (JCPDS No. 80-1098), can be confirmed to belong to the (100) crystal plane of naphthosite. This indicates the presence of carbon and naphthosite-type manganese dioxide (also known as manganese oxide). Studies of manganese oxide materials with different deposition times revealed that when the deposition time increased from 15 min to 30 min, the intensity of the (100) crystal plane diffraction peak increased, while when the deposition time was extended to 60 min and 120 min, the intensity of the (100) crystal plane diffraction peak hardly changed. This indicates that the crystal phase of the prepared material did not change significantly after a deposition time of 30 min, reaching the maximum deposition time.

[0052] Scanning electron microscopy (SEM) analysis:

[0053] Field emission scanning electron microscopy was used to study CPF-loaded MnO x Observe its morphology and structure. For example Figure 3 The results in -a show that unloaded carbon polyurethane foam has a framework composed of an interconnected network and a macroscopic porous structure, which can effectively reduce the wind pressure drop per unit thickness in practical applications. Under MnO loading... x Afterwards, as Figure 3 As shown in -(be), CPF@MnO x Compared to CPF, it exhibits a relatively rougher surface, with the macropores in the original CPF structure being covered. This phenomenon reflects the fact that MnO... x Successful growth of CPF@MnO was observed on the CPF framework. It was also found that the material loading increased with increasing deposition time, structurally altering the coverage of macroscopic channels and causing three-dimensional framework fracture. In comparison, CPF@MnO was successfully grown with a deposition time of 30 min. x ( Figure 3 -c) successfully loaded MnO x It also effectively protects the 3D porous structure of the CPF carrier.

[0054] Formaldehyde removal performance analysis:

[0055] 100 CPF@MnO samples of 10*10mm size were prepared. x The molded material was placed in a 50L sealed reaction chamber and its formaldehyde removal performance at an initial concentration of 10ppm was tested under the conditions of room temperature of 25±2℃ and relative humidity (RH) of 55~65%. The formaldehyde removal rates of different materials are shown in Table 1.

[0056] Table 1:

[0057] Formaldehyde removal rate 60.16% 81.32% 49.37% 42.68%

[0058] Example 3:

[0059] Compared with Example 1, the only difference is that the synthesis temperature in step (4) is changed. Other operations and parameters are the same as in Example 1. The experimental groups are as follows:

[0060] Group A: 40℃, denoted as CPF@MnO x -40℃;

[0061] Group b: 60℃, denoted as CPF@MnO x -60℃ (i.e., Example 1);

[0062] Group C: 90℃, denoted as CPF@MnOx -90℃.

[0063] The formaldehyde removal study for low concentrations was conducted according to the method in Example 1, and the results are shown in Table 2.

[0064] Table 2:

[0065] Formaldehyde removal rate 40.65% 81.32% 70.61%

[0066] Example 4:

[0067] Compared with Example 1, the only difference is that the ultrasonic power in step (4) is changed. Other operations and parameters are the same as in Example 1. The experimental groups are as follows:

[0068] Group A: 500W, denoted as CPF@MnO x -500W;

[0069] Group b: 1000W, denoted as CPF@MnO x -1000W (i.e., Example 1);

[0070] Group C: 1500W, denoted as CPF@MnO x -1500W.

[0071] The formaldehyde removal study for low concentrations was conducted according to the method in Example 1, and the removal rate is shown in Table 3.

[0072] Table 3:

[0073] Formaldehyde removal rate 50.14% 81.32% 62.38%

[0074] Example 5:

[0075] Compared with Example 1, the only difference is that the microwave power in step (4) is changed. Other operations and parameters are the same as in Example 1. The experimental groups are as follows:

[0076] Group A: 300W, denoted as CPF@MnO x -300W;

[0077] Group b: 600W, denoted as CPF@MnO x -600W (i.e., Example 1);

[0078] Group C: 1000W, denoted as CPF@MnO x -1000W.

[0079] The formaldehyde removal study for low concentrations was conducted according to the method in Example 1, and the removal rate is shown in Table 4.

[0080] Table 4:

[0081] Formaldehyde removal rate 71.68% 81.32% 68.37%

[0082] Example 6:

[0083] Compared with Example 1, the only difference is that in step (2), solution A and solution B are not pre-mixed to form solution C, and in step 3, carbon polyurethane foam and solution B are pre-mixed before adding solution A, and then step 4 is performed. All other operations and parameters are the same as in Example 1.

[0084] The test was conducted according to the method in Example 1, and the result was that the formaldehyde removal rate reached 85.37%.

[0085] Example 7:

[0086] Compared with Example 1, the only difference is that the weight ratio of three-dimensional carbon polyurethane foam and potassium permanganate is changed. All other operations and parameters are the same as in Example 1. The experimental groups are as follows:

[0087] Group A: 1:1, denoted as CPF@MnO x -1;

[0088] Group b: 1:2, denoted as CPF@MnO x -2;

[0089] Group C: 1:4, denoted as CPF@MnO x -4.

[0090] The formaldehyde removal study for low concentrations was conducted according to the method in Example 1, and the removal rate is shown in Table 5.

[0091] Table 5:

[0092] Formaldehyde removal rate 51.47% 81.32% 60.37%

[0093] Example 8

[0094] Compared with Example 1, the only difference is that the weight ratio of potassium permanganate and carbohydrate compound is changed to 1:0.1 or 1:0.2; other operations and parameters are shown in Table 6.

[0095] Table 6:

[0096] Formaldehyde removal rate 78.51% 77.68%

[0097] Comparative Example 1: Single polyurethane foam

[0098] (1) Cut the prepared 3mm thick carbon polyurethane foam into 10*10mm squares, and then soak them in 1M dilute nitric acid for 6 hours to promote the oxidation and hydrolysis of its surface groups and enhance its surface hydrophilicity. Then ultrasonically clean it with deionized water until the water is neutral, and dry it to obtain modified CPF.

[0099] (2) The modified CPF from step 1 was subjected to formaldehyde removal test according to the method in Example 1. The results are shown in Table 5.

[0100] Comparative Example 2: Single C / MnO x

[0101] Compared with Example 1, the only difference is that step 1 is missing and CPF is not added in step 3. All other operations and parameters are the same as in Example 1 to obtain C / MnO. x ;

[0102] Other operations, parameters, and testing methods are the same as in Example 1, and the results are shown in Table 7.

[0103] Comparative Example 3: Oven Heating

[0104] Compared with Implementation 1, the only difference is that step (4) was not performed with the assistance of ultrasound and microwave. All other operations, parameters and test methods are the same as in Implementation 1. The results are shown in Table 7.

[0105] Comparative Example 4

[0106] Compared with Example 1, the only difference is that in step (1), activated carbon is used to replace the CPF. All other operations, parameters and test conditions are the same as in Example 1. The results are shown in Table 7.

[0107] Comparative Example 5:

[0108] The materials of Comparative Example 1 and Comparative Example 2 were physically mixed in the proportion of the composite material of Example 1, and the formaldehyde removal test was performed according to the method of Example 1. The results are shown in Table 7.

[0109] Table 7

[0110] Removal rate 81.38% 19.80% 47.76% 69.74% 49.90% 58.42

[0111] The preparation method of this invention can achieve a good catalytic degradation removal rate and removal capacity of formaldehyde at low temperature, and has excellent technical effects.

Claims

1. A method for preparing three-dimensional carbon polyurethane foam@sodium manganese ore material, characterized in that, The three-dimensional carbon polyurethane foam is subjected to surface oxidation treatment; the surface-oxidized three-dimensional carbon polyurethane foam is placed in a reaction vessel, and water-soluble sugars are pre-adsorbed into the surface-oxidized three-dimensional carbon polyurethane foam, which is then mixed with potassium permanganate solution in the liquid phase. After liquid-phase mixing, the reaction is carried out under the assistance of ultrasound and microwave to obtain the three-dimensional carbon polyurethane foam@sodium manganese ore material. During the reaction, the ultrasonic power was 980~1020W, the microwave power was 500~700W, the temperature was 55~65℃, the time was 25~35min, and the weight ratio of three-dimensional carbon polyurethane foam to potassium permanganate was 1:1.5~2.

5. The three-dimensional carbon polyurethane foam has a mesh size of 10~30 PPI and a tensile strength of 0.1~0.2 MPa. The surface oxidation treatment includes immersing the three-dimensional carbon polyurethane foam in a dilute nitric acid solution, followed by washing with water until neutral and drying. The carbohydrate compound is at least one of glucose, sucrose, and chitosan; The aforementioned three-dimensional carbon polyurethane foam@water sodium manganese ore material is a formaldehyde removal material used to remove formaldehyde from the gas to be treated, wherein the initial formaldehyde content in the gas to be treated is below 20 ppm.

2. The preparation method of the three-dimensional carbon polyurethane foam@sodium manganese ore material as described in claim 1, characterized in that, The concentration of the dilute nitric acid is 0.5~3M; Soaking time is 2 to 10 hours.

3. The preparation method of the three-dimensional carbon polyurethane foam@sodium manganese ore material as described in claim 1, characterized in that, The weight ratio of three-dimensional carbon polyurethane foam to potassium permanganate is 1:1.8~2.

2.

4. The preparation method of the three-dimensional carbon polyurethane foam@sodium manganese ore material as described in claim 3, characterized in that, The weight ratio of potassium permanganate to carbohydrate compounds is 1:0.1~0.

2.

5. The preparation method of the three-dimensional carbon polyurethane foam@sodium manganese ore material as described in claim 4, characterized in that, The weight ratio of potassium permanganate to carbohydrate compounds is 1:0.13~0.

18.

6. The preparation method of the three-dimensional carbon polyurethane foam@sodium manganese ore material as described in claim 5, characterized in that, The weight ratio of potassium permanganate to carbohydrates is 1:0.14~0.16; After the reaction is complete, solid-liquid separation is performed, followed by water washing, alcohol washing, and drying to obtain the three-dimensional carbon polyurethane foam@sodium manganese ore material.

7. A three-dimensional carbon polyurethane foam@sodium manganese ore material prepared by the preparation method according to any one of claims 1 to 6.

8. The application of a three-dimensional carbon polyurethane foam@sodium manganese ore material prepared by the preparation method according to any one of claims 1 to 6, characterized in that, It is used as a formaldehyde removal material to remove formaldehyde from the gas to be treated; The initial formaldehyde content in the gas to be treated is below 20 ppm.

9. The application as described in claim 8, characterized in that, The initial formaldehyde content in the gas to be treated is 10~15 ppm; The initial humidity of the gas to be treated during the removal process is 55-65%; The temperature during the removal process is room temperature.

Citation Information

Patent Citations

  • Method for inactivating and regenerating layered manganese dioxide catalyst for degrading formaldehyde at room temperature

    CN115845876A

  • MnO2-based formaldehyde removal material, ultrasonic-microwave assisted preparation method thereof and application of MnO2-based formaldehyde removal material in catalytic oxidation of formaldehyde

    CN114452974A